KESULTANAN TIDORE : BUKTI ARKEOLOGI SEBAGAI PUSAT KEKUASAAN ISLAM DAN PENGARUHNYA DI WILAYAH PERIFERI - Wuri Handoko; Syahruddin Mansyur (Berkala Arkeologi, 2018)
Abstract The sultanate of Tidore is not only an area of Islamic influence residing in Tidore Island, as it is widely understood all along. Tidore Sultanate, is actually one of the centers of Islamic power that has a broad influence to other areas in the Maluku Islands and in Papua. Tidore with Ternate, is the most developed region, as both are able to expand influence and control other areas. This study is a literature study, through historical data and archaeological data from previous studies, to explain the development of the Tidore Sultanate as a center of power and influence in the Tidore power periphery region. The results of the study explain, based on historical data and archaeological evidence, Tidore developed as a center of power with the character of a sultanate city, and has a broad influence to other areas both in the Maluku Islands and in Papua which is the periferinya territory or the territory of Tidore Sultanate.